Racial Discrimination and White First Name Adoption: Evidence from a Correspondence Study in the Australian Labour Market - Shyamal Chowdhury; Evarn Ooi; Robert Slonim (Institute of Labor Economics (IZA), 2020)
We design and implement a correspondence study where we sent fictitious résumés with Chinese names and White names in response to both high-skilled and low-skilled job advertisements. Consistent with similar research elsewhere, we find that there is a large gap in getting interview offers when résumés with first and last Chinese names are used compared to résumés with White first and last names. To tease apart whether the gaps can be better explained by statistical or taste-based discrimination, we also sent out résumés of 'Adopters' with a Chinese last name but White first name. The benefit of having an adopter name was economically meaningful, reducing the gap by about the same amount as would occur if the applicant with a Chinese first and last name had instead received an additional year of honours education. To examine the extent and nature of discrimination, we collected two data sets with administrative population statistics. The administrative information shows that Adopter names signal different characteristics, including educational outcomes and parent background which is consistent with statistical discrimination. In addition, the pool of Chinese applicants is a mixture of international and domestic applicants with the domestic pool being higher achievers whereas the international applicants are much lower achievers. This mixture might be disadvantaging the domestic pool and providing an economic motive for becoming an Adopter. We discuss how our results may help formulate policies for parental investments and employers' education to reduce employment and wage gaps observed between minorities and majorities in labour markets.
Keywords: J15; J71; J64; C93; 330; racial discrimination; correspondence study; labour market; administrative records